Wacława Oszajcy poetycka kontemplacja arcydzieł malarstwa - Wzorek, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The article discusses poetic reflection of Wacław Oszajca on the masterpieces of world painting. In his lyric, the priest-poet describes paintings belonging to the classics of painting: Mona Lisa by Leonardo da Vinci, paintings by Rembrandt (Return of the prodigal son, Sacrifice of Abraham), Hans Memling’s triptych The Last Judgment, and The Last Supper of Salvador Dali. His poems are very short, they are always an attempt to capture the dramatic character of the scene. Among the analyzed poems by Oszajcy, the most interesting, the most valuable one seems to be the work about the image of Rembrandt The return of the prodigal son. It brings accusation of the title character; the author omits important biblical themes - mercy and remorse. Oszajca’s poem describes not only masterpieces of painting, but also serves to recall the lesser known paintings – Crayer or Marian Malarz.
Wacław Oszajca’s Poetic Contemplation of Painting Masterpieces
Keywords: Wacław Oszajca; ekphrasis; priestly poetry; the classics of European painting; contemporary poetry; ekfraza; poezja kapłańska; klasyka malarstwa europejskiego; poezja współczesna